Ethnocentrism Analysis of Indonesian Consumers based on Demographic Factor - Sutisna Muhari; Uli Wildan Nuryanto (Budapest International Research and Critics University, 2022)
Social class of consumers will be the differentiator of the level of ethnocentrism of consumers, who initially used to buy domestically made products, with an increase in income, their buying behavior changed to prefer foreign-made luxury brands. This study aims to analyze ethnocentrism of Indonesian consumers based on demographic factor. The research design to be carried out is to use a quantitative, verification and conclusive approach. This is based on the existence of research problems that question the influence of one variable on other variables. In addition, the research that will be conducted also intends to verify the hypothesis based on the empirical data that will be collected. In addition to the main approach, this research also uses a descriptive approach, especially to answer descriptive problems. The result of this study that differences in the level of consumer ethnocentrism based on demographic variables indicate that older consumers tend to have higher ethnocentrism levels than younger consumers. Meanwhile, based on gender, there is no significant difference in ethnocentrism between men and women.